2022
DOI: 10.1080/21655979.2022.2068921
|View full text |Cite
|
Sign up to set email alerts
|

GATA binding protein 1 recruits histone deacetylase 2 to the promoter region of nuclear receptor binding protein 2 to affect the tumor microenvironment and malignancy of thyroid carcinoma

Abstract: The tumor microenvironment (TME) and activated angiogenesis in thyroid carcinoma (TC) are critical for tumor growth and metastasis. Nuclear receptor binding protein 2 ( NRBP2 ) has been suggested as a tumor suppressor. This study examines the function of NRBP2 in the progression of TC and the regulatory mechanism. By analyzing bioinformatic tools including GSE165724 dataset and the Cancer Genome Atlas system, we predicted NRBP2 as a poorly ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…GATA family of TF1 GATA-binding protein 1 (GATA1) recruited HDAC2 to NRBP2 promoter sequences to suppress the expression of NRBP2 [27] . NRBP2 overexpression suppressed the growth of TC cells, M2 polarization of macrophages, and angiogenesis in TC [42] .…”
Section: The Mechanism Of Hdac2-promoted Tumorigenesismentioning
confidence: 95%
See 2 more Smart Citations
“…GATA family of TF1 GATA-binding protein 1 (GATA1) recruited HDAC2 to NRBP2 promoter sequences to suppress the expression of NRBP2 [27] . NRBP2 overexpression suppressed the growth of TC cells, M2 polarization of macrophages, and angiogenesis in TC [42] .…”
Section: The Mechanism Of Hdac2-promoted Tumorigenesismentioning
confidence: 95%
“…Decreased nuclear receptor-binding protein 2 (NRBP2) expression was observed in thyroid cancer (TC) tissues and cells [42] . Low levels of NRBP2 predicted the poor prognosis of patients with TCs [42] .…”
Section: The Mechanism Of Hdac2-promoted Tumorigenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of the HDACs on the PTC is shown in Figure 3 . In fact, HDAC1 and HDAC2 expression levels are mildly increased in PTC tissues relative to normal tissues ( 37 ), Nuclear receptor binding protein 2 (NRBP2) reduces TC tumorigenesis and M2 macrophage infiltration in vivo , GATA binding protein 1 recruits HDAC2 to the NRBP2 promoter region, inhibits NRBP2 expression by reducing H3K9ac levels, blocks NRBP2 inhibition in PTC histiocytes and BCPAP and TPC-1 cell lines, and thereby promotes the formation of tumor microenvironment(TME) and activates angiogenesis ( 38 ). A META analysis showed that SIRT1 overexpression was detrimental to the overall survival of patients with solid malignancies ( 39 ), and SIRT1 nuclear staining was approximately 2.5-fold higher in PTC tissues than in normal tissues.…”
Section: Histone Deacetylation and Papillary Thyroid Cancermentioning
confidence: 99%